Litter Composting to Meet Fertilizer Needs for Plantation Crops in Asah Duren Village, Jembrana-Bali - Muliarta I Nengah; Desak Ketut Tristiana Sukmadewi; I Made Suarta; Ni Putu Anom Sulistiawati (Asian Journal of Community Services, 2023)
The community service program implemented in Asah Duren Village, Pekutatan District, Jembrana-Bali Regency aims to improve farmers' knowledge and skills in plantation litter management. Another goal is to invite farmers to start utilizing litter and processing it into compost to meet fertilizer needs. The methods used in the service program are observation, socialization, and demonstration. Based on observations, farmers in Asah Duren Village have not used litter, because they still view litter as waste material and have no benefits. Farmers after receiving socialization and training on litter utilization through the plot demonstration method have a desire to process litter into compost. Farmers also want to start using litter compost to reduce the use of inorganic fertilizers. Farmers' interest in utilizing litter compost is also increasing because the price of inorganic fertilizers is increasing